Entrepreneurial Choice of Investment Capital for House-based Industries: A Case Study in West Bengal (India). (December 2015) - Mukherjee, Shrabani
The lack of access to formal credit at affordable cost is the most critical constraint faced by the rural entrepreneurs to get involved in business activities. This study captures the binding constraints for entrepreneurs to obtain their investment capital from subsidised formal credit market. A binary probit model confirms that formal and informal credit behave as imperfect substitutes for investment and an ordered probit analysis claims that huge complexity in lending process of formal sector becomes a major restraint to access the institutional credit and thus makes the formal credit costlier than alternative sources to use it for industrious purposes.